Answer:
x= 2.14 y= -2.71
Step-by-step explanation:
8x + 3y = 9 --------------------equ i
3x - 5y = 20--------------------equ ii
using substitution method
making x the dsubject of formula in 8x + 3y = 9
8x= 9-3y
x=(9-3y)/8-----------------------equ iii
insert it in equ ii
3x - 5y = 20
3{(9-3y)/8} - 5y = 20
open the bracket and add 5y to both sides
27-9y/8= 20+5y
cross multiply
27-9y = 8(20+5y)
27-9y = 160+40y
choose like terms
-9y-40y=160-27= 133
-49y=133
y=133/-49= -2.71
insert the value of y back in x=(9-3y)/8
x=(9-3y)/8= 9-3(-2.71)/8= 9+8.14/8= 17.14/8= 2.14
x= 2.14
or
using elimination system
multiply the coefficient of y (3) in equ i by equation ii
multiply the coefficient of y (5) in equ ii by equation i
5 x 8x + 3y = 9
3 x 3x - 5y = 20
40x+15y=45
9x-15y=60
add each other(since they have different signs + and -)
40x+15y=45
+
9x-15y=60
40x+9x +15y+(-15y) = 45+60
49x = 105
x= 105/49 = 2.14
since x = 2.14 insert it in either equ i or ii
8x + 3y = 9
8(2.14)+3y=9
17.14+3y= 9
17.14-9 = -3y
8.14= -3y
y= 8.14/-3= -2.71
3x - 5y = 20
3(2.14)-5y=20
6.428-5y= 20
6.428-20 = 5y
-13.5714= 5y
y = -13.5714/5 = -2.71